Financial Risk Management in Agriculture : Analyzing Data from a New Module of the Global Findex Database - Klapper, Leora; Singer, Dorothe; Ansar, Saniya; Hess, Jake (World Bank, Washington, DC, 2019)
The ability to manage financial risk is especially important for people earning their living through agriculture. Many farmers only get paid once or twice a year, and households need to stretch their earnings across the year by saving or borrowing money. Moreover, agricultural production faces a variety of risks related to both production and markets because of their exposure to weather and disease shocks. Households engaged in agriculture may thus especially benefit from financial inclusion—access to and use of formal financial services. This paper explores the topic of financial risk management in agriculture—how adults who rely on growing crops or raising livestock as their household's main source of income manage financial risk and use financial services. The paper summarizes new data based on a nationally representative survey of about 15,000 adults in 15 lower-middle- and low-income Sub-Saharan African economies collected as part of the World Bank's Global Findex database. The majority of these adults reported suffering a bad harvest or significant livestock loss in the past five years, and most bear the entire financial risk of such a loss. Most adults in agricultural households lack the financial tools -- such as insurance, accounts, savings, and credit -- that could help them manage financial risks.